Assessing the Impact of Air Pollution in North Macedonia: A Meteorological and Green Infrastructure Study - Srbinovska, Mare; Andova, Vesna; Krkoleva, Aleksandra; Celeska, Maja; Viktor Andonovic; Martin Majstoroskи; Matej Kutirov (My University, 2023)
This paper presents a meteorological and green infrastructure study to evaluate the impact of air pollution in North Macedonia. The study focuses on the spatial and temporal patterns of air pollution in the country and it investigates the influence of various factors on air pollution mitigation. Namely, it considers the effects of the pandemic, as well as measures that tackle air pollution directly, or have other broader goals, but still impact air pollution. The paper utilizes a variety of data sources, including meteorological data – temperature, humidity, wind speed and direction; air quality monitoring data – concentrations of particulate matter (PM), nitrogen dioxide (NO2) and carbon monoxide (CO); and existence and influence of green infrastructure. In addition, the study incorporates advanced statistical and geospatial techniques to create an accurate assessment of the impacts of air pollution in North Macedonia. The statistical analyses reveal the correlations between the collected data and their statistical significance. The investigation confirms the negative correlation between PM on one side and higher air temperatures/wind speed on the other. It provides evidence of the higher concentrations of pollutants during night hours. The positive effects of reduced traffic and use of fossil fuels for heating in winter months are also observed with the analyses of the acquired data. The results of the analyses are used to discuss possible directions for air pollution reduction.